Causes of Socioeconomic Disparities in Colorectal Cancer and Intervention Framework and Strategies - Carethers, John M; Doubeni, Chyke A (Gastroenterology (New York, N.Y. 1943), 2020)
Colorectal cancer (CRC) disproportionately affects people from low socioeconomic backgrounds and some racial minorities. Disparities in CRC incidence and outcomes might result from differences in exposure to risk factors such as unhealthy diet and sedentary lifestyle; limited access to risk-reducing behaviors such as chemoprevention, screening, and follow-up of abnormal test results; or lack of access to high-quality treatment resources. These factors operate at the individual, provider, health system, community, and policy levels to perpetuate CRC disparities. However, CRC disparities can be eliminated. Addressing the complex factors that contribute to development and progression of CRC with multicomponent, adaptive interventions, at multiple levels of the care continuum, can reduce gaps in mortality. These might be addressed with a combination of health care and community-based interventions and policy changes that promote healthy behaviors and ensure access to high-quality and effective measures for CRC prevention, diagnosis, and treatment. Improving resources and coordinating efforts in communities where people of low socioeconomic status live and work would increase access to evidence-based interventions. Research is also needed to understand the role and potential mechanisms by which factors in diet, intestinal microbiome, and/or inflammation contribute to differences in colorectal carcinogenesis. Studies of large cohorts with diverse populations are needed to identify epidemiologic and molecular factors that contribute to CRC development in different populations.